Gambaran Pelaksanaan Kewaspadaan Universal di Puskesmas Kolongan Kabupaten Minahasa Utara - Ottay, Ronald I.; Palandeng, Henry Malcom Frank; Porajow, Zwingly Christian J.G.; Rompas, Putri M.B. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Background: Universal Precautions are prevention acts that must be done by all of the health workers to prevent the infection spreading from the patients or vice versa. The purpose of this research is to measure the overview of the implementation of universal precaution in Kolongan Community Health Center. Method: The research method is surveillance descriptive research with total sampling method as the sample collecting method. Result: Accumulatively, there were (9.44%) of all the respondents do not always wash their hand appropriately according to the washing hands procedures and indications. For about (10.57%) do not always wear protective items either in cleaning up medical instruments or doing examination to patients. We found out that (13.33%) do not always decontaminate equipments and devices properly before and after using them. Nevertheless, all of the respondents agreed that there are proper needles and sharps disposals, and all of the respondents always dispose all needles and other sharps promptly to each of their disposals. Also, all of the respondents agreed that there are separated disposals for medical and non medical wastes, and all of the respondents always dispose the wastes properly to the separately disposals. Conclusion: in Kolongan Community Health Center, the overview of the implementation of universal precautions is good. Keywords: Universal Precautions, Infection, Kolongan Community Health Center.